(untitled) (Revista Argentina de Musicología, 2018)
The 78 rpm records during the life of the “acoustic” recording system and even in the early years of the new “electric” system were not recorded at 78 rpm speed, but between 66 and 82 rpm. However, playback devices, since 70 years ago, rotate at 78 rpm. This speed variation when playing discs produces pitch and tempo variations with respect to the version played “live” when recording was made. Such variation can be up to three semitones, and involves timbre deformation of voices and instruments. This problem has been known for a long time but is not considered by those who study popular music in Argentina, with some exceptions. This situation leads to a misevaluation of a high percentage of recordings made between 1905 and c. 1930, that are not heard properly, deforming the perception of the current analyst. Despite being a highly technical (mechanical) issue it should not be overlooked, since it affects the aesthetic perception greatly. The article explains this problem, proposes a solution and suggests the necessary rewriting of many aspects of the history of the tango of the first two decades of the twentieth century, based on a critical evaluation of existing phonograms.